Research of Resources Search Mechanism on Hybrid Stream Media System - Dagang Guo; Mingqin Zhuo; Jirong Zhang (Dianxin kexue)
A hybrid resources search mechanism based on the popularity of resources was proposed in the hybrid peer to peer stream media system based on CDN and P2P.A different search mechanism was used according to the different popularity of resources，such as structured search or flooding.By this way，the efficient of search was effectively improved.In the part of structured search，an improved Chord search mechanism was proposed.Compared with the traditional Chord search mechanism，the router delay was greatly reduced.A flooding search mechanism based on bloom filter was proposed in the part of flooding.Compared with the traditional flooding search mechanism，it can significantly lower the redundancy transmission of search request.Also，according to the different popularity of resources，multi-keyword query and the concept of semantic correlation were proposed to support fuzzy search，and the rate of successful search was greatly increased.